Effects of natalizumab on oligoclonal bands in the cerebrospinal fluid of multiple sclerosis patients: A longitudinal study. (December 2014) - Mancuso, R; Franciotta, D; Rovaris, M; Caputo, D; Sala, A; Hernis, A; Agostini, S; Calvo, MG; Clerici, M
Retrospective studies show that natalizumab modifies oligoclonal immunoglobulin (IgG) bands (OCBs) in the cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients. In this study, we prospectively analyzed both serum and CSF samples from 24 MS patients, before and after 2 years of natalizumab-based therapy. Our results showed complete (55%) or partial (27%) disappearance of the OCBs in CSF samples that were taken after 2 years of therapy. Intrathecal IgG production, represented by the IgG index and IgGLoc, was also quantitatively reduced. Our data showed that natalizumab substantially modulates both intrathecal polyclonal and oligoclonal IgG production: This effect was much more potent than was previously reported.